1997
DOI: 10.1046/j.1365-2605.1997.00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequently subnormal semen profiles of normal volunteers recruited over 17 years

Abstract: In order to establish semen profiles for men in the general population, we analysed the semen parameters of 187 men attending the Institute of Reproductive Medicine between 1977 and 1993 as volunteers for clinical studies. If several ejaculates were obtained from the volunteer, only the first ejaculate was used for analysis. More than half of the ejaculates of these healthy men showed at least one abnormal parameter, so that only 46% of the volunteers could be classified as being 'normozoospermic' according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
2
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 0 publications
1
26
2
1
Order By: Relevance
“…Whereas several studies reported an agedependent decrease in the sperm concentration [7,[21][22][23][24][25], others were not able to confirm such findings [9,20,26,27]. In the present study, the sperm concentration was found to be significantly higher in group IV than in groups II and III and significantly higher in group I than in group II.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Whereas several studies reported an agedependent decrease in the sperm concentration [7,[21][22][23][24][25], others were not able to confirm such findings [9,20,26,27]. In the present study, the sperm concentration was found to be significantly higher in group IV than in groups II and III and significantly higher in group I than in group II.…”
Section: Discussioncontrasting
confidence: 87%
“…In fact, motility was reported to decrease by 0.7% per year of age [21]. Several studies reported a significant decrease in the sperm motility with advancing age [16,23,[25][26][27], whereas others found an increase in the sperm motility with age [31,32]. Several studies on infertile groups, however, revealed no significant evidence of deteriorating sperm motility with advancing age [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have illustrated an increase in concentration of 0.3%-3.3% per year of age [24][25][26][27] while another subset of reports details no association with paternal age. 14,18,28,29 The difficulty in analyzing concentration data, however, is the concomitant change in semen volume that may occur with APA.…”
Section: Effect Of Paternal Age On Semen Qualitymentioning
confidence: 99%
“…[8][9][10][11] On the other hand, fertile men may also be investigated for infertility and subsequently treated as a result of their low semen quality. 12,13 To establish evidence-based reference values, the WHO 2010 manual describes the values obtained in eight countries from 1953 men who became fathers with a time to pregnancy of less than 12 months. Therefore, this is a population of fertile men whose spouses were of high or normal fecundity and who established a pregnancy in f12 months.…”
Section: The Semen Analysis (Who 2010)mentioning
confidence: 99%